Bank Influence at a Discount - Gersbach, Hans; Papageorgiou, Stylianos (Journal of Financial and Quantitative Analysis, 2024)
Abstract In a general equilibrium framework, we show that banks may “buy” political influence at a discount: They offer disproportionately small campaign contributions compared to the influence they exert, thus generating abnormal returns. We distinguish between the direct effect of contributions which, as a cost, reduce bank returns, and the indirect effect of contributions which boost returns via inducing bank-favoring policies. Therefore, abnormal returns may or may not increase with the amount of contributions, depending on which effect dominates: Stricter capital requirements decrease contributions and abnormal returns. When politicians attach more weight to households’ welfare, contributions increase and abnormal returns decrease.